Finite Element Analysis for Design Engineers - Kurowski, Paul M. (SAE International, 2023)
Finite Element Analysis (FEA) has been widely implemented by the automotive industry as a productivity tool for design engineers to reduce both development time and cost. This essential work serves as a guide for FEA as a design tool and addresses the specific needs of design engineers to improve productivity. It provides a clear presentation that will help practitioners to avoid mistakes. Easy to use examples of FEA fundamentals are clearly presented that can be simply applied during the product development process.